A CAUSAL MODEL OF FACTORS AFFECTING HIGH PERFORMANCE ORGANIZATION OF COLLEGES AND UNIVERSITIES IN SHENYANG UNDER LIAONING PROVINCE - Yuze, Liu; Chaisirithanya, Kamolmal; Chinatangku, Chuanchom (วารสารวิจัยธรรมศึกษา, 2024)
The objectives of this research were: (1) to examine components of the high performance organization(HPO) of colleges and universities in Shenyang, Liaoning Province; (2) to develop a causal model of factors affecting high performance organization(HPO) of colleges and universities in Shenyang, Liaoning Province; and (3) to verify the causal model of factors affecting high performance organization of colleges and universities in Shenyang, Liaoning Province with empirical date . The research was a mixed methodology research. The Population consisted of 4844 people who were managers and teachers They came from 3 colleges and universities of different school categories in Shenyang, Liaoning Province, which are classified according to school type. The researcher determined sample size with Krejcie and Morgan’s Table (1970). The sample size was 357. The key informants were five experts, obtained by purposive sampling method. The instruments used for data collection were Analysis of literature content and five-point survey scale. The statistics used for date analysis were descriptive statistics, correlation analysis, and regression analysis to analyze the collected data, Confirmatory Factor Analysis (CFA), and Structural equation model (SEM). The research findings revealed that; (1) the components of high-performance organizations in universities in Shenyang, Liaoning Province were identified;HPO consist of nine components:leadership, excellent talent team, a good working environment, clear goals and performance orientation, efficient communication and collaboration, continuous learning and innovation, emphasize teacher development and satisfaction, incentive and reward mechanism, organizational culture and values (2) a causal model for high-performance organizations in colleges and universities were developed and verified its rationality;and (3)Leadership positively impacted direct and indirect high-performance organizational performance through motivation. Motivation directly enhanced performance, while its impact on Organizational commitment was limited. Organizational commitment directly improved performance. Leadership’s indirect impact on high-performance organizations operated through motivation and organizational commitment. Leadership incentives had a limited impact on Organizational commitment in high-performance organizations.